The breakdown of the Grand Alliance and the origins of the Cold War, 1942-1946 - Kent, John 1949- (Cambridge Scholars Publishing, 2024)
"This book challenges the standard orthodox and neo-revisionist accounts of the origins of the Cold War, which portray the West as containing an expansionist Soviet Union. Initially showing the importance of all three major wartime leaders attached to cooperation in the post-war international order, the book then focuses on imperial rivalries, particularly between Britain and the Soviet Union in the Balkans and Eastern Mediterranean, but also between the US and the Soviet Union in East AsiaThe book provides a nuanced account, evaluating the responsibilities of the three major Allies for the breakdown of wartime cooperation by covering in detail the issues in Germany, Poland, Romania, Greece, Iran and Egypt. It thereby provides an analysis of specific interests to enable an accurate chronology of leaders' and foreign ministers' conferences. Uniquely, it treats Britain's role as comparatively more important in the alliance's breakdown and the Cold War's origins."
Keywords: Geschichte 1942-1946; Ost-West-Konflikt; Alliierte; Zweiter Weltkrieg; World War, 1939-1945 / Diplomatic history